2017
DOI: 10.1017/dmp.2017.50
|View full text |Cite
|
Sign up to set email alerts
|

Acute Chemical Incidents With Injured First Responders, 2002-2012

Abstract: All responders should have at least basic awareness-level hazardous material training to recognize and avoid exposure. Research on improving firefighter PPE should continue. (Disaster Med Public Health Preparedness. 2018;12:211-221).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 9 publications
1
21
0
1
Order By: Relevance
“…Elevations in CO have been documented in biomonitoring among both urban and wildland firefighters [ 1 , 3 , 16 ]. Furthermore, this has been observed despite reported compliance with personal protective equipment use requirements [ 17 ]. Because work-related CO exposure risk can be mitigated but not necessarily eliminated among firefighters, taking into account concomitant sources of exposure in this group can be particularly relevant to occupational health management for such workers.…”
Section: Discussionmentioning
confidence: 99%
“…Elevations in CO have been documented in biomonitoring among both urban and wildland firefighters [ 1 , 3 , 16 ]. Furthermore, this has been observed despite reported compliance with personal protective equipment use requirements [ 17 ]. Because work-related CO exposure risk can be mitigated but not necessarily eliminated among firefighters, taking into account concomitant sources of exposure in this group can be particularly relevant to occupational health management for such workers.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have found that the prevalence of appropriate respiratory protection was low among emergency responders to the World Trade Center collapse ( 7 ). A recent analysis of ATSDR surveillance data found that, among 1,275 emergency personnel with known PPE status who were injured or became ill during acute hazardous substance release incident responses during 2002–2012, only 382 (30.0%) wore some type of respiratory protection ( 8 ). Respiratory protection prevalence was 45.8% among injured firefighters, compared with 1.4% among police and 2.3% among emergency medical services personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Almost twice as many incidents occurred in fixed facilities (8,711) than during transportation (4,818). In addition, nonfatally injured persons were approximately 10 times more frequently associated with a fixed-facility incident (4,523) than a transportation incident (421).…”
Section: Incident Characterizationmentioning
confidence: 99%
“…They are often injured in chemical incidents and are not always wearing PPE. One study found that many first responders were injured in chemical incidents while responding to illegal methamphetamine laboratories (8). First responders might be exposed to a diverse array of chemicals.…”
Section: Public Health Implicationsmentioning
confidence: 99%
See 1 more Smart Citation